Cemented Calcar-Guided Short-Stem Prostheses in Geriatric Patients: Short-Term Results from a Prospective Observational Study - Bertram Regenbrecht; Ahmed Yaseen; Gideon Wagener; Michael Wild (MDPI AG, 2024)
Both cementless and cemented stems have exhibited favorable long-term outcomes in total hip arthroplasty. Nonetheless, in elderly patients, cemented hips offer an advantage due to their reduced risk of periprosthetic fractures. This study aimed to assess the initial outcomes of 28 patients who underwent unilateral cemented total hip arthroplasty utilizing a calcar-guided A2 stem (ARTIQO GmbH, Lüdinghausen, Germany). Various types of antibiotic-loaded bone cement were employed. During follow-up, we recorded demographic data and comorbidities and employed standardized clinical assessment tools, including the Harris Hip Score. Radiographic assessments included preoperative, postoperative, and follow-up imaging to evaluate subsidence, osteolysis, and bone resorption. The results indicated that among the 28 patients, 5 withdrew consent and 2 patients passed away from unrelated causes. Additionally, one prosthesis was explanted due to the undersizing of the cement stopper, which resulted in an inadequate cement mantle. As a result, 20 patients underwent a 1-year follow-up, revealing noteworthy enhancements in clinical scores, with no instances of radiolucent lines or osteolysis. No infections were detected. In summary, our short-term experience with this particular cemented short-stem design yielded promising results, exhibiting excellent functional outcomes, no aseptic loosening attributable to the stem, and no infections. Further clinical studies and registry data are essential to corroborate these findings.